Economic Impact Of Program Growth Shopee Agent Jombang - Fitri Rohmah; Imam Sopingi; Kusnul Yuni (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2026)
This study aims to analyze the economic impact of the Shopee agent program in Sumbermulyo Village, particularly in increasing income and employment opportunities for the local community. The method used was qualitative, with a survey approach involving Shopee agents and the surrounding community, as well as secondary data analysis related to village economic development. The results show that the Shopee agent program has made a positive contribution to the local economy through the creation of new jobs, increasing agent income, and expanding community access to digital products. However, challenges remain, such as potential economic inequality and pressure on traditional local traders. The implications of this study emphasize the importance of developing similar programs in other areas to encourage the digitalization of the rural economy, improve digital literacy, and create inclusive policies that support all economic actors, including local traders. These findings are relevant for the government, e-commerce companies, and MSMEs in designing digital-based economic development strategies.